2021
DOI: 10.1073/pnas.2110190118
|View full text |Cite
|
Sign up to set email alerts
|

SAMD9L autoinflammatory or ataxia pancytopenia disease mutations activate cell-autonomous translational repression

Abstract: Significance The experiments here advance understanding of the function of the SAMD9L gene and protein in innate immune mechanisms in resisting virus infection and in the pathogenesis of inflammatory, hematological, and neurological disorders. The clinical syndrome defined in two children with de novo truncating SAMD9L mutations expands the phenotypes in this newly recognized autoinflammatory disorder. Analysis of cells expressing normal or mutant SAMD9L reveals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 38 publications
10
28
0
1
Order By: Relevance
“…Whole-exome sequencing analysis of the patient revealed the SAAD-associated de novo c.2658-2659del, p.F886Lfs*11 mutation of SAMD9L gene, confirmed by Sanger sequencing. 3,5 The present case highlights the benefit of early HSCT in SAAD, as reported in the literature (Table S2), 3,[5][6][7] showing its limits on extra-hematological manifestations. The absence of acute graftversus-host disease and the low acute toxicity displayed by our patient after alpha/beta/CD19-depleted haplo-HSCT may suggest this approach as a valid therapeutic strategy.…”
Section: Progression Of Non-hematologic Manifestations In Samd9lassoc...supporting
confidence: 75%
See 1 more Smart Citation
“…Whole-exome sequencing analysis of the patient revealed the SAAD-associated de novo c.2658-2659del, p.F886Lfs*11 mutation of SAMD9L gene, confirmed by Sanger sequencing. 3,5 The present case highlights the benefit of early HSCT in SAAD, as reported in the literature (Table S2), 3,[5][6][7] showing its limits on extra-hematological manifestations. The absence of acute graftversus-host disease and the low acute toxicity displayed by our patient after alpha/beta/CD19-depleted haplo-HSCT may suggest this approach as a valid therapeutic strategy.…”
Section: Progression Of Non-hematologic Manifestations In Samd9lassoc...supporting
confidence: 75%
“…The present case highlights the benefit of early HSCT in SAAD, as reported in the literature (Table ), 3,5–7 showing its limits on extra‐hematological manifestations. The absence of acute graft‐versus‐host disease and the low acute toxicity displayed by our patient after alpha/beta/CD19‐depleted haplo‐HSCT may suggest this approach as a valid therapeutic strategy.…”
Section: Gene Loss Of Function Gain Of Functionsupporting
confidence: 68%
“…Together, our data demonstrated that inflammation potentiates Samd9l-Mut phenotypes, in particular, pancytopenia with lymphopenia, corresponding to clinical observations in patients with SAMD9L mutations (13,(29)(30)(31).…”
Section: Inflammation Augments B Cell Lymphopenia and Impairs Erythro...supporting
confidence: 79%
“…They are interferon-responsive genes, and their expression dramatically increases following exposure to interferons (IFN) and TNFα (10)(11)(12). In addition to the germline mutations observed in patients with BMF and myeloid neoplasms, SAMD9L mutations have also been associated with inflammatory diseases (13).…”
Section: Introductionmentioning
confidence: 99%
“…SAMD9L-SAAD is a new entity previously described in eight patients whose clinical features overlap with CANDLE4 5 (see online supplemental file 1). The overall phenotype of patients is very severe as three out of eight patients deceased at an early age and three other one of them underwent bone marrow transplantation for severe cytopenia or intersticial lung disease (ILD).…”
mentioning
confidence: 99%